An unexpected aziridination/rearrangement/oxidation tandem reaction leading to the total synthesis of (−)-mersicarpine. Issue 29 (20th July 2017) - Zhang, Yun; Xue, Yibin; Luo, Tuoping
Abstract: With the aim to synthesize anti-mitotic natural product (−)-rhazinal, we proposed a strategy based on a dearomative intramolecular [3+2] cycloaddition between alkyl azide and indole, followed by rearrangement to furnish the featured tetracyclic framework. During the reaction condition screening, we accidentally encountered a tandem [3+2] cycloaddition/rearrangement/oxidation reaction, which enabled the synthesis of another alkaloid, (−)-mersicarpine, in four steps with 35% overall yield from a reported intermediate. The tandem [3+2] cycloaddition/rearrangement reaction disclosed herein could provide a method for the synthesis of other structurally intriguing alkaloids. Graphical abstract: